2014
DOI: 10.2463/mrms.2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

Splenial and White Matter Lesions Showing Transiently-reduced Diffusion in Mild Encephalopathy Monitored with MR Spectroscopy and Imaging

Abstract: We report the time course of magnetic resonance imaging and spectroscopy of a case with lesions of the splenium and white matter with transiently reduced diffusion in clinically reversible encephalopathy. Initially normal spectroscopy showed slightly elevated choline. Signal abnormality in T 2 -weighted and fluid-attenuated inversion recovery images persisted for 90 days. Lesions of the splenium and white matter with transiently reduced diffusion in clinically reversible encephalopathy are not always reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Normal NAA and no significant peaks of lip and Glx suggested that normal neuronal integrity was preserved, without evidence of irreversible neuro-axonal damage [23,25,]. These results are consistent with the limited available MRS studies of transient SCC lesions, suggesting that a reversible intramyelinic citotoxic edema could represent the main pathophysiologic mechanism 355 [19,[46][47][48].…”
Section: Discussionsupporting
confidence: 59%
“…Normal NAA and no significant peaks of lip and Glx suggested that normal neuronal integrity was preserved, without evidence of irreversible neuro-axonal damage [23,25,]. These results are consistent with the limited available MRS studies of transient SCC lesions, suggesting that a reversible intramyelinic citotoxic edema could represent the main pathophysiologic mechanism 355 [19,[46][47][48].…”
Section: Discussionsupporting
confidence: 59%
“…On diffusion tensor imaging, only slight change on diffusion anisotropy has been demonstrated . On MRS, normal/near normal spectrum with normal N ‐acetyl‐aspartate (NAA) further supports transient intramyelinic edema over neuroaxonal damage or severe demyelination . It is unclear why there is increased vulnerability of the splenium of the CC, and there is no definite difference in fiber composition of the splenium when compared with the remainder of the CC .…”
Section: Reversible Splenial Lesionsmentioning
confidence: 99%
“…Of the persisting or residual cases, 22 were in adults and five in children. Rarely, CLOCC persisted without major changes (number of patients = 2; 1%) until their follow-up at 1 month [ 2 ] and 3 months [ 11 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One hundred twenty-five publications included children only, comprising a total of 937 children. Their median age was 5.1 years (IQR [4][5][6][7][8][9][10][11][12].…”
Section: Eligible Publications and General Study Characteristicsmentioning
confidence: 99%